The Influence of Changes in the Logo and Slogan of PT Aplikasi Karya Anak Bangsa on Achieving Brand Image Among Consumers in Medan City - Abdul Gafur; Zulkarnain, Iskandar; Lubis, Suwardi (Talenta Publisher, 2024)
This study aims to analyze the effect of changing the logo and slogan of PT Aplikasi Karya Anak Bangsa on the achievement of brand image among Medan city consumers. The theory used in this study is the theory of communication, new media, advertising, brand, rebranding and brand image. The research method used is a quantitative method with explanatory research. The population in this study are consumers of theGojek application in the city of Medan. The sampling technique uses the Taro Yamane formula so that a total sample of 100 respondents is obtained with the sample criteria, namely consumers of the Gojek application in the city of Medan who know the changes to the Gojek logo andslogan. The data collection technique used in this study was field research by distributing questionnaires and library research. The data analysis technique used is descriptive analysis, classical assumption test, multiple linear regression analysis and hypothesis testing. The results showed that there was an effect of changing the logo and slogan of PT Aplikasi Karya Anak Bangsa on the achievement of brand image among Medancity consumers. The magnitude of the influence or the coefficient of determination of changes in the Gojek logo and slogan on brand imageachievement is 46.2%, which means the correlation is quite significant,Â while the remaining 53.8% is the influence of other factors not examined in this study such as service quality, trust, reliability and speed. Â